WELFARE EFFECTS OF LIVELIHOOD DIVERSIFICATION OF FARM HOUSEHOLDS IN NORTHERN GHANA: A QUANTITATIVE APPROACH - Zakaria, A.; Azumah, S. B.; Donkoh, S. A. (UDS International Journal of Development, 2019)
The declining trends of agricultural productivity in Northern Ghana, which could be attributed in part to climate change, is pushing farm-households to add non-farm livelihood activities to their existing on-farm livelihood activities in order to survive. The extent to which this diversification is affecting the livelihoods of farm households is not fully understood in the empirical literature. This paper therefore explores the effect of livelihood diversification on farm households’ welfare. By using multistage sampling procedure, 284 farm households from 62 communities in the Northern and Upper East regions of Ghana were used for the study. The Probit model was employed to examine factors influencing farm households’ decision to diversify their source of livelihoods. The Propensity Score Matching (PSM) was employed to estimate the effects of livelihood diversification on farm households’ welfare. The probability of diversifying was higher for older farmers, farmers with access to extension service, male farmers, farmers who perceived that rainfall was erratic and that temperatures were high. Using household off-farm income as a proxy for welfare, the PSM results indicate that on the average, diversified farm households are better off (GHȻ2,657.52 per annum) compared to non-diversified farm households (GHȻ2,448.95 per annum). This study therefore recommends that farm households across Northern Ghana should diversify their sources of income to reduce liquidity constraint to enhance farm productivity via the purchase of productivity enhancing farm inputs. Keywords: Diversification, Welfare, Off-farm income, Probit model, PSM, Northern Ghana